Medications at the Emergency Department After Recent Rape - Gilmore, Amanda K. (Journal of interpersonal violence, 2022)
Rape is associated with myriad negative physical and mental health effects, yet little is known about medical prescribing following rape-related emergency room visits. The goal of this study was to examine factors associated with medications prescribed the same day as a sexual assault medical forensic examination (SAMFE). A total of 939 medical records (93.9% female) of a medical university in the Southeastern United States between July 1, 2014, and May 15, 2019, were paired with Sexual Assault Nurse Exam records. Demographic and assault characteristics were examined as correlates of medications prescribed at the emergency department within the same day of a SAMFE. All individuals were offered medications within the national guidelines. Intimate partner violence (IPV) was negatively associated with antibiotic prescriptions and with emergency contraception prescriptions. Genital injury and male gender of victim were positively associated with antiviral prescriptions. Non-genital injury was positively associated with both over-the-counter and prescription pain medication prescriptions. Report of strangulation was positively associated with accepting over-the-counter but not prescription pain medication. IPV and strangulation were positively associated with psychotropic prescriptions. Although specific medications were offered to individuals during the SAMFE, demographic and assault characteristics were associated with medication acceptability.